2022
DOI: 10.3389/fphys.2022.1052429
|View full text |Cite
|
Sign up to set email alerts
|

Endocrinal metabolic regulation on the skeletal system in post-menopausal women

Abstract: Osteoporosis is a common endocrinologic disorder characterized as a chronic bone loss condition. Sexual dimorphism is ubiquitous in the incidence of osteoporosis with post-menopausal women being acutely affected. Gonadal sex hormones including estrogen act as crucial regulators of bone mass; therefore, loss of such hormones leads to an imbalance in skeletal turnover leading to osteoporosis. Estrogen can influence both bone formation as well as resorption by reducing osteoblast activity and enhancing osteoclast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 104 publications
(93 reference statements)
0
13
0
Order By: Relevance
“…Postmenopausal osteoporosis, as the most prevalent type of low bone mass, seriously affects approximately 10% of women aged more than 60 years, contributing to increased morbidity and significant loss of independence in the long run. 22 The serum 5-HT level is a negative predictor of total and trabecular volumetric BMD and plays a physiological role in the regulation of bone mass. 23 The present study elicited that 5-HT precursors and metabolite are inversely associated with lumbar spine and femoral neck BMD and positively correlated with bone turnover markers PINP and β-CTX in PMOP women.…”
Section: Discussionmentioning
confidence: 99%
“…Postmenopausal osteoporosis, as the most prevalent type of low bone mass, seriously affects approximately 10% of women aged more than 60 years, contributing to increased morbidity and significant loss of independence in the long run. 22 The serum 5-HT level is a negative predictor of total and trabecular volumetric BMD and plays a physiological role in the regulation of bone mass. 23 The present study elicited that 5-HT precursors and metabolite are inversely associated with lumbar spine and femoral neck BMD and positively correlated with bone turnover markers PINP and β-CTX in PMOP women.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies carried out in both OVX rodents and postmenopausal women have demonstrated that oestrogen deficiency induces bone loss and osteoporosis, which is mainly characterized by decreased BMD 5,47 and a significant increase in bone turnover (both formation and resorption) markers. 30,47,92 These bone-related alterations are normally counteracted or ameliorated after HRT treatment.…”
Section: Food and Function Papermentioning
confidence: 99%
“…The decline and gradual cessation of oes-trogen production by loss of ovarian follicular activity and function 1 occurring during the menopausal transition and menopause can cause a variety of vasomotor symptoms, such as hot flushes, sleep disturbances and night sweats. [2][3][4] In addition, this ageing process may be associated with osteoporosis, 5 increased body weight and a change in body fat distribution from a gynoid to an android pattern, contributing to increased abdominal fat accretion. [6][7][8] This excess of adiposity can exacerbate the appearance of metabolic alterations such as hypercholesterolemia, hypertension and insulin resistance, increasing the risk of suffering cardiovascular diseases (CVDs), [6][7][8][9][10] which become more evident with age and are one of the leading causes of death worldwide, accounting for 47% of deaths in women.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, estrogen deficiency not only directly affects the differentiation of precursor cells more toward active osteoclasts and less toward osteoblasts but can also influence their cellular energetics. Increased adiposity and inflammation after menopause can indirectly lead to bone loss as well [ 14 ].…”
Section: Introductionmentioning
confidence: 99%